Improving The Quality of Effective Sermoning: Through Spiritual Direction, Material Preparation, Personal Readiness - Runesi, Adrian Aurolyan Parsautan; Hutagalung, Stimson (Peneliti.net, 2025)
Sermons play an important role in Christian worship, where sermons are an educational medium to proclaim the truth of God's word. The sermon highlights important aspects of Christianity. According to the theory of homiletics, a sermon is a profound theological work and must adhere to the Bible, with the power of the Holy Spirit as the main authority in the power of preaching. Elements of effective preaching include spiritual and theological direction through the true word and the power of the Holy Spirit, preparation of material and structure through biblical exegesis, thematic outlines, contextual illustrations, and the use of creative technology, as well as personal and communication readiness that includes mental-emotional-spiritual aspects, training, voice intonation, body language, and overall thoroughness. The research method uses qualitative approaches, literature review, and Research and Development to compile a systematic blueprint to help assess and improve the quality of the sermons. This research aims to develop effective preacher models in the contemporary world